ROS‐responsive thioether‐containing hyperbranched polymer micelles for light‐triggered drug release. Issue 3 (1st February 2022) - Wang, Guanchun; Huang, Ping; Wang, Lei; Chen, Xinliang; Zhou, Yongfeng; Huang, Wei; Yan, Deyue
Abstract: As a kind of promising drug carriers, smart polymers have attracted much attention due to the effective and controlled drug release in target cells. Herein, a reactive oxygen species (ROS)‐responsive thioether‐containing amphiphilic hyperbranched polymer prepared from MTPA and TMPTGE (HBPMT) is synthesized from 3‐(methylthio)propylamine (MTPA) and trimethylolpropane triglycidyl ether (TMPTGE) by the amine‐epoxy click reaction via A2 + B3 one‐pot approach. Benefiting from its inherent amphiphilic nature, HBPMT can self‐assemble into stable micelles in water. Triggered by H2 O2, these micelles can be dissociated rapidly because hydrophobic thioether segments in their cores are oxidized into hydrophilic sulfoxide or sulfone groups. Additionally, the ROS produced by photosensitizer under light irradiation can also play the same role of H2 O2 . Such HBPMT micelles can be utilized to encapsulate anticancer drug paclitaxel (PTX) and photosensitizer chlorin e6 (Ce6) simultaneously for drug delivery and control release. The methyl thiazolyl tetrazolium assay toward MCF‐7 tumor cells (a human breast adenocarcinoma cell line) indicates that these micelles encapsulated with PTX and Ce6 exhibit a significant combinational efficacy of cell proliferation inhibition, which means the promising potential for synergistic chemo‐photodynamic cancer therapy. Such a novel nanocarrier based on amphiphilic to hydrophilic transition would provide a candidate for controlled drug release and cancer combination therapy. Abstract : In this study, a thioether‐containing amphiphilic hyperbranched polymer prepared from MTPA and TMPTGE (HBPMT) is synthesized from 3‐(methylthio)propylamine (MTPA) and trimethylolpropane triglycidyl ether (TMPTGE) and can self‐assemble into spherical micelles to coload photosensitizer chlorin e6 (Ce6) and anticancer drug paclitaxel (PTX). Under 660 nm light irradiation, 1 O2 generated by Ce6 can oxidize the hydrophobic thioether segments in HBPMT into hydrophilic sulfoxide or sulfone groups to cause rapid dissociation of HBPMT micelles and release of PTX, indicating a significant combinational efficacy of cell proliferation inhibition.